Determinants of consumers’ purchase intentions of electronic vehicles - Nombulelo DILOTSOTLHE (Indonesia Strategic Sustainability, 2022)
Electric vehicles are being introduced as a sustainable innovative solution, aimed at eliminating the negative environmental effects by having the ability to reduce carbon emissions, air pollution and fossil fuel dependency. It is therefore important for management, marketers and government to find innovative ways to promote and increase the adoption rate of these vehicles. This paper aims to make use of the theory of consumption values to predict the purchase intention for plug-in hybrid electric vehicles (PHEVs) in Gauteng, South Africa. Using structured questionnaire and convenience sampling, data was collected from 286 respondents. Online data collection was used due to the Coronavirus pandemic restrictions, which limited the researchers’ abilities to explain items in the questionnaire. A partial least squares structural equation modelling was performed to test the proposed hypotheses. Results indicate that functional, social, emotional and conditional values are positively related to customers’ purchase intention of PHEVs, while the epistemic value is not positively related. This study will provide useful information to electric vehicle manufacturers, car dealerships, marketing managers and the government in developing strategies aimed at encouraging the adoption of PHEVs.